2013
DOI: 10.1210/er.2012-1081
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Tissue in Adult Humans: A Metabolic Renaissance

Abstract: Brown adipose tissue (BAT) plays a key role in energy homeostasis and thermogenesis in animals, conferring protection against diet-induced obesity and hypothermia through the action of uncoupling protein 1 (UCP1). Recent metabolic imaging studies using positron emission tomography computerized tomography (PET-CT) scanning have serendipitously revealed significant depots of BAT in the cervical-supraclavicular regions, demonstrating persistence of BAT beyond infancy. Subsequent cold-stimulated PET-CT studies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
0
61

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(195 citation statements)
references
References 232 publications
6
128
0
61
Order By: Relevance
“…It has been also found in neonates of large mammalian species and more recently, in adults (Lee et al, 2013). As observed in human, BAT depots in sheep are mainly found in the supraclavicular/ neck region and in the pericardial and perirenal regions (Symonds et al, 2015).…”
Section: Overview Of Structure Location and Functions Of Adipose Tismentioning
confidence: 71%
“…It has been also found in neonates of large mammalian species and more recently, in adults (Lee et al, 2013). As observed in human, BAT depots in sheep are mainly found in the supraclavicular/ neck region and in the pericardial and perirenal regions (Symonds et al, 2015).…”
Section: Overview Of Structure Location and Functions Of Adipose Tismentioning
confidence: 71%
“…PET-FDG is a functional exam characterized by its ability to detect metabolically active areas that uptake FDG, a glucose radioisotope (23,30,31). It began being used in the 90s, mainly in oncology, to detect tumors and metastases, which generally have a high metabolic rate and therefore high glucose uptake.…”
Section: Pet-fdg: the "Denouncer" Of Brown Adipose Tissuementioning
confidence: 99%
“…Although the total mass of brown adipose tissue in mammals is small, past research has already demonstrated that its activation could quadruple the energy expenditure (EE) of an animal, as an increase in tissue perfusion occurs (15,(21)(22)(23). Not only the fat stored in its lipid droplets are used to generate heat, but also free fatty acids and glucose from systemic circulation, exponentially increasing its thermogenic capacity (15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations